Distribution And Antimicrobial Susceptibility Of ESBL Positive Enterobacteriaceae Isolates In Various Clinical Specimens Of Patients Admitted In Critical Care Areas - HENA RANI; RAMAN SARDANA; PRASAD RAO P. VOLETI; RADHA RANI (International Journal of Pharma and Bio Sciences, 2012)
Extended spectrum β-lactamases (ESBLs) pose a major problem in clinical therapeutics as infections caused by the organisms producing such enzymes are associated with a higher morbidity and mortality. Critical care areas (CCA) in a hospital are the high pressure area where the microbes isolated may be multidrug resistant. The present study was undertaken at a tertiary care healthcare setup in New Delhi, India to look for the distribution of ESBLs producing Enterobacteriaceae isolates in various clinical specimens of patients admitted in CCA and to study their antimicrobial susceptibility pattern. A total of one hundred Enterobacteriaceae isolates from CCA were studied. The strains were identified by API system and their antimicrobial susceptibility was tested by API and VITEK systems. ESBLs production was detected by CLSI, Double Disc Diffusion (DDS) and Vitek methods. The maximum number of Enterobacteriaceae isolates was obtained from respiratory tract (50%) but maximum ESBLs positivity was seen in isolates from blood stream infections (85%). ESBLs production was seen in 66% isolates. The antibiotic resistance rate was more for ESBLs positive isolates in comparison to ESBLs negative isolates. Detection of ESBLs producing strains should be routinely done in clinical microbiology laboratory to prevent misuse of antimicrobials leading to large scale benefits to society.